Amorfização de ilmenita para preparação de material adsorvente poroso e sua aplicação na remoção de corante em ambiente aquoso - Figueiredo, Pietro Serraglio (2024)
In this work, natural ilmenite (ILM) was amorphized by alkaline fusion (I550) with NaOH at 550 ºC and alkaline activation (I60) at 60 ºC. The materials ILM, I60 and I550 were characterized through XRD, FTIR, SEM/EDS and BET analyses. XRD showed partial and complete amorphization for samples I60 and I550, respectively. SEM/EDS confirmed the amorphization of the material and the fusion of NaOH in the composition of the I550 material. The increase in the surface area of the materials produced was obtained by BET, varying from 5.90 m² g-1 to 28.14 m² g-1 for the I60 material and 88.84 for m² g-1 for I550. The materials were tested as adsorbents by removing crystal violet (VC) dye from an aqueous matrix. The best material obtained was I550 due to its greater surface area and porous structure, with optimal conditions of adsorbent dosage of 0.3 g L-1 and pH 9. These intrinsic characteristics of the material obtained (I550) resulted in satisfactory adsorption capacities worth 133 mg g-1 at 328 K. Kinetic studies on the adsorption process indicated that the material reached equilibrium in around 50 min, with the model being from AVRAMI who best described the process. Adsorption thermodynamics revealed that the adsorption of VC on I550 is spontaneous, endothermic, and favorable. The amorphized material maintained its performance after three cycles of reuse. Therefore, the amorphization route proposed in this work was satisfactory, producing a porous adsorbent from the mineral ilmenite, with potential use for wastewater treatment.